Evaluation of cardiac autonomic dysfunctions in children with type 1 diabetes mellitus - Davut Gözüküçük; Berkut A. İleri; Serra Karaca Başkan; Ece Öztarhan; Dilek Güller; Hasan Önal; Kazım Öztarhan (BMC, 2024)
Abstract Background Cardiovascular autonomic neuropathy (CAN) is a serious complication of diabetes, impacting the autonomic nerves that regulate the heart and blood vessels. Timely recognition and treatment of CAN are crucial in averting the onset of cardiovascular complications. Both clinically apparent autonomic neuropathy and subclinical autonomic neuropathy, particularly CAN pose a significant risk of morbidity and mortality in children with type 1 diabetes mellitus (T1DM). Notably, CAN can progress silently before manifesting clinically. In our study, we assessed patients with poor metabolic control, without symptoms, following the ISPAD 2022 guideline. The objective is is to determine which parameters we can use to diagnose CAN in the subclinical period. Methods Our study is a cross-sectional case-control study that includes 30 children diagnosed with T1DM exhibiting poor metabolic control (average HbA1c > 8.5% for at least 1 year) according to the ISPAD 2022 Consensus Guide. These patients, who are under the care of the pediatric diabetes clinic, underwent evaluation through four noninvasive autonomic tests: echocardiography, 24-h Holter ECG for heart rate variability (HRV), cardiopulmonary exercise test, and tilt table test. Results The average age of the patients was 13.73 ± 1.96 years, the average diabetes duration was 8 ± 3.66 years, and the 1-year average HbA1c value was 11.34 ± 21%. In our asymptomatic and poorly metabolically controlled patient group, we found a decrease in HRV values, the presence of postural hypotension with the tilt table test, and a decrease in ventricular diastolic functions that are consistent with the presence of CAN. Despite CAN, the systolic functions of the ventricles were preserved, and the dimensions of the cardiac chambers and cardiopulmonary exercise test were normal. Conclusions CAN is a common complication of T1DM, often associated with the patient's age and poor glycemic control. HRV, active orthostatic tests, and the evaluation of diastolic dysfunctions play significant roles in the comprehensive assessment of CAN. These diagnostic measures are valuable tools in identifying autonomic dysfunction at an early stage, allowing for timely intervention and management to mitigate the impact of cardiovascular complications associated with T1DM.